If it's not what You are looking for type in the equation solver your own equation and let us solve it.
126-3(6x-6)=0
We simplify the equation to the form, which is simple to understand
126-3(6x-6)=0
Reorder the terms in parentheses
126+(-18x+18)=0
Remove unnecessary parentheses
+126-18x+18=0
We move all terms containing x to the left and all other terms to the right.
-18x=0-126-18
We simplify left and right side of the equation.
-18x=-144
We divide both sides of the equation by -18 to get x.
x=8
| 4c+6=5c-9 | | 4x^2-76=3x | | 2x2y0(5xy2)2/5(-2xy2) | | 4x^2-7=-27x | | 5f+3= | | 5p=p-6 | | y=177-8x | | 4(4y+9)=50 | | 3a+10=a+38 | | 24x^2+22x+3=0 | | 4(x-1)-3=13 | | 8-18x=2-x | | 2-3(-9)=-7 | | 19.45=-8.6r+-12.8 | | 4t-8+14t=3-4t-11 | | 3v+19=5v-17 | | 2-3(5)=-7 | | 12s+20=17s | | 19a-8=15a | | 4/5-(-16/5) | | -5(8a-6)=-34-8 | | 2z+20=3z-9 | | 3p+13=p+15 | | p=5.65-.05(78.4) | | 328=8(6+5a) | | 5w-14=4w+4 | | X=5y*7 | | 3(x-1)=5x+4 | | 2x-k=-1 | | X-5=2(x-20) | | 5.65-.05q=.75+.0125q | | 2-3(2)=-7 |